Technical feasibility studies for Langkawi WCO (waste cooking oil) derived-biodiesel - Kumaran P.; Mazlini N.; Hussein I.; Nazrain M.; Khairul M. (Elsevier Ltd, 2023)
A study has been done to consider Malaysian WCO (waste cooking oil) generated in an eco-tourism island, Langkawi, Malaysia as an alternative feedstock for biodiesel production. This paper presents the results of the comprehensive technical feasibility study for production of biodiesel from WCO feedstock. The results have shown feasibility of recycling WCO into biodiesel that is compliant with international fuel standard ASTM D6751. The study has given an indication on the appropriate processing scheme to be developed for recycling WCO into biodiesel as a substitute fuel for diesel vehicles in Langkawi that would enable the promotion of alternative fuel in the energy mix for long term environment sustainability. 2011 Elsevier Ltd.